Kick back and destroy the ride: Alcohol-related violence and associations with drinking patterns and delinquency in adolescence - Stafström Martin (BMC, 2007)
Abstract Aim To assess how drinking patterns and delinquency are associated with self-reported experiences of alcohol-related violence in an adolescent population. Population and research design Cross-sectional data were acquired from the Scania drug use survey 2005, consisting of 3847 students in 9th grade. Abstainers were omitted and 1873 responses analyzed, with binary and multi-variable logistic regression modeling. Results All drinking pattern indicators were statistically significantly associated with alcohol-related violence, high usual volume of distilled spirits consumed (OR 2.2, CI 95 % 1.7-2.9) being the strongest. Delinquency had, when included in the analysis, a significant effect (OR 2.5, CI 95 % 1.8-3.6); however, the drinking pattern indicators also remained statistically significant. An analysis of the effect moderation between usual volume of distilled spirits consumed and delinquency showed that there was a synergetic effect between them (SI 1.6, CI 95 % 1.1-2.4). A separate analysis for non-delinquent students, those with little experience of delinquency, and those who engaged regularly in delinquent activities, showed that the effects of different drinking patterns, especially use of distilled spirits, were significant in both groups, however, differently distributed. Conclusion The results show that alcohol consumption pattern, with usual volume of distilled spirits being the most prominent one, had an effect on alcohol-related violence, and that this effect was amplified by delinquent behavior. The analyses also showed that there are similarities, regarding risk factors for alcohol-related violence, between delinquent and non-delinquent youth. This, indicating that consumption pattern cannot be discarded as a key factor in alcohol-related violence in adolescence. Policy implications The study shows that alcohol-related violence in adolescence is related to both alcohol consumption patterns, e.g. usual volume of distilled spirits consumed, and delinquency. In order to prevent the harm outcome, both phenomenons have to be targeted, either by alcohol or broader social policy initiatives.